Therapeutic effects of ritual ayahuasca use in the treatment of substance dependence: qualitative results - Loizaga-Velder, Anja; Verres, Rolf (Journal of psychoactive drugs, 2014)
This qualitative empirical study explores the ritual use of ayahuasca in the treatment of addictions. Ayahuasca is an Amazonian psychedelic plant compound created from an admixture of the vine Banisteriopsis caapi and the bush Psychotria viridis. The study included interviews with 13 therapists who apply ayahuasca professionally in the treatment of addictions (four indigenous healers and nine Western mental health professionals with university degrees), two expert researchers, and 14 individuals who had undergone ayahuasca-assisted therapy for addictions in diverse contexts in South America. The study provides empirically based hypotheses on therapeutic mechanisms of ayahuasca in substance dependence treatment. Findings indicate that ayahuasca can serve as a valuable therapeutic tool that, in carefully structured settings, can catalyze neurobiological and psychological processes that support recovery from substance dependencies and the prevention of relapse. Treatment outcomes, however, can be influenced by a number of variables that are explained in this study. In addition, issues related to ritual transfer and strategies for minimizing undesired side-effects are discussed.